Gunnar and Mrs. Kasson with Balto - Cole, Joseph E. (Cleveland Memory Project, 1925)
"Two heros of Alaska arrive. Gunnar and Mrs. Kasson, with Balto, arrive at Seattle, Wash. to begin work on a motion picture. Kasson was the intrepid dog sled driver who made the last lap of the race against death in Nome, Alaska, with the life saving diphtheria anti-toxin. Balto, his lead dog, smelt cut the trail in a howling blizzard after his master had become blinded by stinging snow, and lead his team of huskies for miles eventually to stagger into Nome."--photo verso.